2015
DOI: 10.1111/1440-1681.12348
|View full text |Cite
|
Sign up to set email alerts
|

Canavanine induces insulin release via activation of imidazoline I3 receptors

Abstract: The aim of the present study was to identify the effect of canavanine on the imidazoline receptor because canavanine is a guanidinium derivative that has a similar structure to imidazoline receptor ligands. Transfected Chinese hamster ovary-K1 cells expressing imidazoline receptors (nischarin (NISCH)-CHO-K1 cells) were used to elucidate the direct effects of canavanine on imidazoline receptors. In addition, the imidazoline I3 receptor has been implicated in stimulation of insulin secretion from pancreatic β-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…Therefore, NISCH seems suitable for use to indicate the imidazoline binding sites and I‐R without subtype specificity. In the present study, similar to another agonist, canavanine, the effects of morin were markedly reduced in MIN6 cells with ablated NISCH, indicating the important role of the I‐R in insulin secretion of morin. Moreover, this view is further supported by the effects of the negative control carbachol on insulin secretion, which was not changed in MIN6 cells with ablated NISCH.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Therefore, NISCH seems suitable for use to indicate the imidazoline binding sites and I‐R without subtype specificity. In the present study, similar to another agonist, canavanine, the effects of morin were markedly reduced in MIN6 cells with ablated NISCH, indicating the important role of the I‐R in insulin secretion of morin. Moreover, this view is further supported by the effects of the negative control carbachol on insulin secretion, which was not changed in MIN6 cells with ablated NISCH.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, we demonstrated that KU14R can inhibit morin‐induced insulin secretion in MIN6 cells at a dose sufficient to block I‐3R . KU14R has been used as the antagonist of I‐3R in some reports .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Thus, canavanine inhibits cell proliferation [20] and induces apoptosis [21,22] in cell cultures, and it also increases susceptibility to radiation in cancer cells [23]. In addition, it inhibits some of the deleterious effects of endotoxic shock in rat models [24,25] and has potential as an antidiabetic agent because it has been found to increase uptake of glucose [26] and release of insulin [27] in cell cultures.…”
Section: Speciesmentioning
confidence: 99%